The Rising Bar for Persecution in Asylum Cases Involving Sexual and Reproductive Harm - Marouf, Fatma E. (Columbia Journal of Gender and Law, 2011)
This Article argues that there is a rising bar for establishing persecution in U.S. asylum cases involving sexual and reproductive harm. Analyzing recent cases, the Article shows that adjudicators tend to apply a higher standard for physical harm in these types of cases and largely overlook nonphysical harm, including psychological suffering and the intangible harm caused by deprivation of equality, autonomy, and privacy. The Article focuses specifically on two types of cases where these patterns appear: (1) female genital mutilation (FGM); and (2) involuntary insertion of an intrauterine device (IUD). Regarding FGM, the Article discusses an emerging dispute as to whether Type I FGM (clitoridectomy) constitutes persecution. With respect to involuntary IUDs, the Article analyzes a decision by the Board of Immigration Appeals (BIA) requiring aggravating circumstances for the harm to constitute persecution, as well as recent circuit court decisions reviewing the application of this problematic precedent to other cases. The Article then argues that using international human rights law to identify and evaluate various types of harm would lead to a much more comprehensive and principled analysis of persecution and would likely lead to different results in these types of cases.